The alcohol consumption of wine drinkers with the onset of Covid-19. (June 2022) - Agnoli, Lara; Charters, Steve
Highlights: First global study of COVID-19 and alcohol use with wine professionals and amateurs. Professionals show a higher likelihood of increased alcohol consumption. Higher likelihood of stability in alcohol consumption among non-professionals. Anxiety affects wine consumption of professionals and beer consumption of amateurs. Age and gender affect the role of anxiety on drinking during the pandemic. Abstract: The onset of Covid-19 has been the most evident global crisis of the current decade so far. This study explores the difference between professionals in the drinks industry and non-professional wine lovers and the impact on their consumption behaviour of wine and other alcoholic beverages in the early stages of the pandemic, particularly in the context of anxiety. A survey by questionnaire was administered worldwide from the end of March to the end of June 2020 to test four research hypotheses. Results are relevant for the alcoholic beverage industry and public policy. They highlight a higher incidence of unchanged alcohol consumption among non-professionals. They also reveal similarities and differences in changes in consumption behaviour and trends among the two cohorts. Anxiety has an impact on the wine consumption of professionals, and on beer consumption of non-professionals, where the gender and age of respondents are also relevant. The findings of a short qualitative data-collection process enrich our understanding of the results.